Brand Image Islamic: Halal Food Product Quality in Relationship To Repurchase Intention - Trihudiyatmanto, M; Prananditya, Ari; Iqbal, Muhammad Amjed (Journal of Digital Marketing and Halal Industry, 2022)
The theory of repurchase intention is one theory that explains customer behavior. Customers respond positively to the quality of service and intend to consume the company's products again. Many researchers study customer behavior influenced by service and product quality, but not much research has been conducted from an Islamic brand image perspective. An Islamic brand image is a form of brand image in the minds of consumers by using Islamic names. This research is causal research, which aims to analyze the relationship and influence of two or more phenomena through hypothesis testing. The sampling technique used was the accidental sampling method. Methods of data collection using a questionnaire using the Linkert scale. After being tested statistically using Structural Equation Modeling (SEM) analysis, the study results show that the quality of halal food products affects repurchase intentions. Islamic Brand Image mediates the effect of the relationship between the quality of halal food products on repurchase intentions at Yuasa Food Wonosobo. The halal aspect is one of the special considerations in the future, and this aspect needs to be developed further.